Nonclonal coloniality: Genetically chimeric colonies through fusion of sexually produced polyps in the hydrozoan Ectopleura larynx. Issue 4 (11th July 2018) - Chang, E. Sally; Orive, Maria E.; Cartwright, Paulyn
Abstract: Hydrozoans typically develop colonies through asexual budding of polyps. Although colonies of Ectopleura are similar to other hydrozoans in that they consist of multiple polyps physically connected through continuous epithelia and shared gastrovascular cavity, Ectopleura larynx does not asexually bud polyps indeterminately. Instead, after an initial phase of limited budding in a young colony, E. larynx achieves its large colony size through the aggregation and fusion of sexually (nonclonally) produced polyps. The apparent chimerism within a physiologically integrated colony presents a potential source of conflict between distinct genetic lineages, which may vary in their ability to access the germline. To determine the extent to which the potential for genetic conflict exists, we characterized the types of genetic relationships between polyps within colonies, using a RAD‐Seq approach. Our results indicate that E. larynx colonies are indeed comprised of polyps that are clones and sexually reproduced siblings and offspring, consistent with their life history. In addition, we found that colonies also contain polyps that are genetically unrelated, and that estimates of genome‐wide relatedness suggests a potential for conflict within a colony. Taken together, our data suggest that there are distinct categories of relationships in colonies of E. larynx, likely achieved through a range of processes including budding, regeneration, and fusion of progeny and unrelated polyps, with the possibility for a genetic conflict resolution mechanism. Together these processes contribute to the reevolution of the ecologically important trait of coloniality in E. larynx .